Review and assessment of offshore renewable energy resources in morocco' coastline. Issue 1 (1st January 2019) - Alaoui, Chakib
Abstract: Modern Morocco's heavy dependence on foreign energy imports, combined with a rapidly growing population and an increasing demand for a better quality of life, makes the country's future uncertain. Possessing rich and diversified renewable energy resources within its territory encouraged the Moroccan government to make ambitious plans to integrate renewable energy resources into its national grid on a big scale, 42% of its energy generating capacity from renewables by 2020, and 52% by 2030. This paper provides a first assessment of the offshore energy potential available near the coastline of Morocco. After a brief description of operations of offshore wind, tidal and wave power, a first order assessment of their potential is presented and discussed. This study shows that important offshore wind resources are available throughout the Mediterranean and the Atlantic coast of Morocco. This resource peaks between the regions of Al Jadida and Agadir, reaching a speed of 9_m/s. The bulk of the offshore resources are located at the Atlantic coastline of the country. Tidal stream resources are concentrated at the region of Tangier, where tidal speed is up to 1.9_m/s potentially producing 1.58_kW/m 2 . Oualidia lagoon was studied and found to be capable of producing more than 0.5_MW of electricity if a tidal barrage exploits 10% of its surface. Finally, ocean wave energy is available all over the Atlantic coastline and peaks between the regions of Essaouira and Agadir where the wave heights are between 1.9 and 2.13_m.